Produksi Briket dari Limbah Plastik dan Ampas Tebu dengan Metode Pirolisis - Pasaribu, Monita; Sena, Muhammad Arya; Kristiani , Maria; Jaman, Winda Sri; Enggita, Asadian Puja; Supardi, Supardi (LPPM Universitas Mataram, 2024)
Plastic is a polymer product that is widely used in society. This resultx in an increase in plastic waste. Plastic waste processing needs to be done to prevent environmental emissions. Plasstic waste can be converted into an alternative energy source in briquettes. The reasearch object is to produce briquettes from plastic and sugarcane bagasse. Plastic briquettes and bagasse have a ratio of 1:2, 1:1 and 2:1. The second stage is the preparation and design of the tool using the pyrolisis method. Research variables include the composition of plastic waste and sugarcane bagasse. Analysis of briquette products includes calorific value, ash conten and water conten. The results of research on briquette products with variations in sampel A having a ratio of 1:2, sample B with ratio of 1:1 and sample C with a ratio 2:1 respectively show a calorific value of 3,929 cal/g, 4.013 cal/g, 4,222 cal/g; water content values of 8,6%, 6,7%, 5,8%, the ash content value is 5,4%, 7,2% and 8,6% and the volatile matter value is 15.3, 13.2% and 12,6%.